Comparison of Fuzzy-AHP and ANP Decision Making Methods to Assess the Ecological Capability of Ecotourism Application (Case study: Dehloran National Natural Monuments) - Mohsen Tavakoli (جغرافیا و پایداری محیط)
The continuous utilization of renewable natural resources involves identifying the ecological potential of the land in any environment, and this identification, with the help of optimal and programmed management, enables the use of resources and prevents environmental degradation. The national natural monuments of Dehloran, in the form of three important national natural effects, including mineral hot springs, natural bitumen springs and bat cave, can provide a suitable platform to attract ecotourism in the region. Therefore, promotion of ecotourism in the area is considered as a supportive tool for conservation and a tool to facilitate its management. Regarding this issue, in this study, the ecological potential of this region has been evaluated for ecotourism use. Ecological capability of these monuments for ecotourism use has been evaluated. After data collection and basic studies, the important criteria of soil, climate, physiographic and vegetation cover are selected. Then, multiple criteria evaluation of FUZZY AHP and ANP methods have been used for standardization and weighting of criteria. Finally, environmental unit map of ecological capability for ecotourism was prepared using Makhdom model and WLC. The results indicated that in FUZZY AHP method, 80 percent of the area is suitable for ecotourism which is more close to reality, but ANP method shows 62 percent accordance. The main result of this research is that FUZZY AHP is more flexible which is powerful for creating ecotourism capability map of such area. Extended Abstract 1-Introduction Ecotourism travels responsibly and sustainably are based on relatively untouched areas in nature to satisfy psychological needs which provide the basis for socio-economic participation, local communities, and have the least negative impact on nature and natural resources. Tourism with the ecotourism approach is considered as a pattern of tourism in nature. This spatial pattern involves the approach of tourists to the natural environment, with different motivations that the tourist is considered in traveling to the natural environment or nature. In the studies of land capability and land use planning for sustainable development, data and maps of various ecological, economic, social and infrastructural parameters are needed for the identification, preparation, analysis and evaluation of them with traditional methods, especially when it comes to multi-purpose use, it is very complicated and time consuming. National natural monuments of Dehloran, including mineral hot springs, natural bitumen springs and bat cave with their natural attractions can provide a suitable platform for tourism attraction in the region, Therefore, promoting ecotourism in the region is considered as a supportive tool for conservation and a tool to facilitate its management. 2-Materials and Methods Iran's ecological model of ecotourism in general represents a three-story power which has been organized within the framework of equations, linear programming. In this model, gradually from class one to class three, the quality and flexibility of land is unsuitable for ecotourism. The present study is based on the ecological parameters (physical and biological) to assess the ecological capability of agriculture land use including physiographic (percent slope) (So), precipitation (Cp), temperature (Ct), distance from water sources (Wc), soil depth (Pd), soil erosion (Es), soil structure (Ps), soil texture (Pte), soil drainage (Pdr) and vegetation types (Vgo). The weighing of information layers is done using the methods of network analysis and fuzzy AHP analysis. After the preparation and preparation of the information layers, the information layers were entered into the geographic information system as a grid and the initial spatial analysis was performed on them. The fuzzy method was then used to determine the membership function. The weights obtained from both methods were applied to the fuzzy layers. Then, to combine the layers, the model of overlapping index or linear weight composition was used. 3-Results and Discussion Using the GIS on the slope of the linear reduction subscription function, the trajectory linear membership function layer and the temperature layer, an incremental linear membership function was applied. Based on the final zoning map of the total area of the region, about 57% is recognized as first class and about 38% in third class for tourism. Through the network analysis process and in the fuzzy AHP method, 5% is recognized as first class and about 16% in third class. In the process of network analysis, the slope has the highest impact and aspect has the minimum impact on the study area which is consistent with the results of Aghdar et al. (2017). Moreover, in the fuzzy AHP method, among the main criteria, vegetation density has the highest and climate has the least effect. Among the soil criteria, under construction criteria and depth, respectively, have the highest and the least impact. According to the final maps, obtained from both methods and their analysis in Google Earth software, regions that are similar in all respects are in the same class in the fuzzy AHP method and in the network analysis process, they are in two different classes, which is not compatible with the existing reality. Using Google Earth software and field observations in the study area, it can be concluded that the results obtained from the fuzzy AHP method are more consistent with the reality of the region. The results also indicate that not only is there a case for expanding tourism activities in the region, but also the conditions of the region for ecotourism are good; it is a more obvious result in the fuzzy AHP method. 4- Conclusion The identification of suitable areas and those with the potential to develop ecotourism in the areas managed by the department of the environment is considered very important for sustainable use of natural resources. The study area in terms of tourism, regional, national and international aspects, is an excellent location with good planning principles and the conditions can be provided to attract ecotourism. Thus, promoting ecotourism in the region, is considered as a safety net to protect and as tools to facilitate the management of national natural monuments of Dehloran. Fuzzy AHP method results indicated the efficacy of this method for studying land use, particularly in the studies of ecological capability evaluation.